1981
DOI: 10.1111/j.1365-2672.1981.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Selenite Cystine and TT Enrichment Broths for the Detection of Salmonella

Abstract: Comparisons of selenite cystine (SC) and TT enrichment broths for detecting salmonellas were made with pure culture suspensions, with samples of naturally or artificially contaminated foods and with poultry feed. Selenite cystine recovered higher numbers of salmonellas from pure cultures and ground beef, while TT broth recovered higher numbers from pork sausage and poultry feed. Differences in the recovery of salmonellas from other food products appeared to be insignificant. The use of both SC and TT is thus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
2
2
0
1
Order By: Relevance
“…typhi. The scanty growth of salmonellas in TB/43 could be due to the potential toxicity of this medium on the growth of these micro-organisms ; this hypothesis agrees with the results obtained by Vassiliadis et al (1974), Harvey and Price (1979), Bailey et al (1981) and D'Aoust (1981.…”
Section: Discussionsupporting
confidence: 90%
“…typhi. The scanty growth of salmonellas in TB/43 could be due to the potential toxicity of this medium on the growth of these micro-organisms ; this hypothesis agrees with the results obtained by Vassiliadis et al (1974), Harvey and Price (1979), Bailey et al (1981) and D'Aoust (1981.…”
Section: Discussionsupporting
confidence: 90%
“…TB medium manufactured by BBL performed somewhat better than TB from the other four manufacturers, but the number of positive recoveries was small and thus unreliable for comparative purposes. Overall, SC appeared superior to TB for recovery of Salmonella from chicken samples, which is consistent with results reported previously (2,4).…”
Section: Salmonellasupporting
confidence: 91%
“…Knowing what types of Enterobacteriaceae are present could be an important factor in determining the most effective bacteriological procedures for recovery of Salmonella from these materials. It has been demonstrated that the types of competing bacteria present may affect the recovery of Salmonella and that these are an important factor to consider in selecting the most effective enrichment media (Hugues et al, 1978;Bailey et al (1981). E. coli are normally present in the chicken gut in large (Cox et al, 1975(Cox et al, , 1979.…”
Section: Resultsmentioning
confidence: 99%